2015
DOI: 10.1002/anie.201500274
|View full text |Cite
|
Sign up to set email alerts
|

Dye‐Controlled Interfacial Electron Transfer for High‐Current Indium Tin Oxide Photocathodes

Abstract: Efficient sensitized photocathodes are highly desired for solar fuels and tandem solar cells, yet the development is hindered by the scarcity of suitable p-type semiconductors. The generation of high cathodic photocurrents by sensitizing a degenerate n-type semiconductor (tin-doped indium oxide; ITO) is reported. The sensitized mesoporous ITO electrodes deliver cathodic photocurrents of up to 5.96±0.19 mA cm(-2), which are close to the highest record in conventional p-type sensitized photocathodes. This is rea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(25 citation statements)
references
References 37 publications
0
23
1
Order By: Relevance
“…Because of the complex structure of crystalline In 2 O 3 , it was thought that the factors that determine the high conductive mechanism and lead to a low resistivity were unclear [176]. Recently, it was found that ITO could both donate and accept electrons in dye-coated ITO films when photoinduced charge transfer occurred [177]. When ITO was modified with elements such as Mg, Ca, Yb, etc., the electrodes maintained their electrical characteristics but increased their ambient stability [178].…”
Section: Indium Tin Oxidementioning
confidence: 99%
“…Because of the complex structure of crystalline In 2 O 3 , it was thought that the factors that determine the high conductive mechanism and lead to a low resistivity were unclear [176]. Recently, it was found that ITO could both donate and accept electrons in dye-coated ITO films when photoinduced charge transfer occurred [177]. When ITO was modified with elements such as Mg, Ca, Yb, etc., the electrodes maintained their electrical characteristics but increased their ambient stability [178].…”
Section: Indium Tin Oxidementioning
confidence: 99%
“…The acute sensitivity of this reaction to the number of TiO 2 electrons present in the nanocrystallite 17 and the very weak driving-force dependence reported by most [19][20][21][22] , but not all 23 , has led many to conclude that observed rate constants report only on the diffusional encounters of the TiO 2 electrons with the molecular acceptors [24][25][26][27] . Clifford et al found that interfacial electron transfer was most easily understood when the physical location of the acceptor frontier molecular orbitals was taken into account 19 , which has been exploited to optimize interfacial electron transfer with highly doped degenerate semiconductors 28 . Collectively, the prior literature is in line with the viewpoint that electron transfer from a semiconductor to a molecular acceptor is sensitive to distance, which naturally raises the question of whether specific interfacial pathways exist.…”
mentioning
confidence: 99%
“… provide overviews of experimental investigations of photoelectrode/molecular catalyst systems. However, many questions remain about the various factors that affect the efficiency of the photoelectrode/molecular catalyst interface such as band‐edge alignment between the photoelectrode and molecular catalyst and between the molecular catalyst and the electrolyte, stable immobilization of the molecular catalyst to the photoelectrode surface, the absence of deleterious surface states, and facile interfacial charge transfer . Therefore, the systematic experimental search for photoelectrode/molecular catalyst systems for water splitting is still a relatively nascent field, even though there are a few comparative studies of experimental catalytic activities and mechanisms of commonly used molecular catalysts .…”
Section: Catalytic Activity Of Functionalized Photoelectrodesmentioning
confidence: 99%
“…The significant computational cost of first‐principles MD, hybrid functional DFT, and MBPT calculations should prompt efforts to formulate widely applicable design rules or heuristics. This may be accelerated by the availability of experimental measurements on a wide variety of photoelectrode/molecular catalyst systems, allowing easy benchmarking and validation of computational methods.…”
Section: Catalytic Activity Of Functionalized Photoelectrodesmentioning
confidence: 99%
See 1 more Smart Citation